Advanced Methods in Material Forming - Banabic, Dorel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The book contains the most relevant papers presented in the International Conference on Materials Forming, ESAFORM 2005. The list below presents some of the most successful minisymposia of the conference: New and advanced numerical strategies in forming process simulation; Sheet metal forming technologies and modeling; Anisotropy and formability of materials; Polymer processing and modeling; Composite forming technologies and modeling; Superplastic forming. Plenary and keynote papers were presented by well-known specialists working in the fields of sheet metal forming technology, automotive industry, modeling of the mechanical behavior as well as the fundamental and industrial research on polymeric materials. This volume gathers selected plenary and keynote papers presented in the conference, offering an up-to-date synthesis of the academic and industrial research in the fields of physical and numerical modeling of materials forming processes. The book is useful for the doctoral fellows, scientists and engineers involved in various domains of materials processing technology.
Constitutive Modeling for Metals -- Material Forming and Dimensioning Problems: Expectations from the Car Industry -- Optimization of the Phenomenological Constitutive Models Parameters Using Genetic Algorithms -- A Metamodel Based Optimisation Algorithm for Metal Forming Processes -- Modelling of Permeability and Mechanical Dispersion in a Porous Medium and Comparison with Experimental Measurements -- Three-Dimensional Bending of Profiles by Stress Superposition -- Specimen for a Novel Concept of Biaxial Tension Test – Design and Optimisation -- Applications of a Recently Proposed Anisotropic Yield Function to Sheet Forming -- Modelling of the Forming Limit Diagrams Using the Finite Element Method -- Recent Advances in Process Design for Sheet and Tube Hydroforming -- Evaluating the Press Stiffness in Realistic Operating Conditions -- Fast Material Working: Wire Drawing -- 3D-ECAP of Square Aluminium Billets -- Computer-Aided Tool Path Optimization for Single Point Incremental Sheet Forming -- Study on the Achievable Accuracy in Single Point Incremental Forming -- On the Finite Element Simulation of Thermal Phenomena in Machining Processes -- Numerical Simulation of Wire Coating Pseudoplastic and Viscoplastic Fluids -- Experimental Study on Behaviour of Woven Composites in Thermo-Stamping Under Nonlinear Temperature Trajectories -- Thixoforming of Steel: Experiments on Thermal Effects -- Study of the Liquid Fraction and Thermophysical Properties of Semi-Solid Steels and Application to the Simulation of Inductive Heating for Thixoforming -- Simulation of Secondary Operations and Springback – The Implicit Shell Provides a Precise and Rapid Solution.
Keywords: Mechanics; Mechanics, Applied; Manufactures; Materials science; Theoretical and Applied Mechanics; Manufacturing, Machines, Tools, Processes; Solid Mechanics; Materials Science, general